The Lightfastness or the Non-Photochemistry of Dyes - Horst E.A. Kramer (CHIMIA)
The following classification of dyes, UV stabilizers, sensitizers, and optical brighteners is proposed in the light of the Jablonski diagram. The fastest deactivation process should be: (a) internal conversion (kIC) for dyes on textile fibres and UV stabilizers acting as absorbers, (b) fluorescence emission (kF) for optical brighteners and laser dyes, and (c) intersystem crossing process (kISC) for sensitizers. – The photochemistry of dyes is discussed according to Koizumi’s classification of D-R, D-D, and D-0 processes (D = dye, R = reducing agent, O = oxygen ). The «reacticity» of the excited singlet and triplet state is defined with respect to the D-R process. While the reactivity of the excited singlet is higher than that of the triplet state (energetic aspect), the triplet state is favoured by its longer lifetime (kinetic aspect). Contributions to the internal conversion were determined separately for some aminoanthraquinone dyes and the following order has been found: inter-molecular hydrogen bonds (from the solvent methanol to the amino and to the carbonyl groups of the dye ) > introduction of a methyl group on the amino moiety > intramolecular hydrogen bond.